Streamlined A* for Faster Robotic Inspections in Ports - Hartanto Kusuma Wardana; Rumaksari, Atyanta; Prischa Wilhelmina Picanussa; Budihardja Murtianta; Adri Sooai; King Harold Recto (Jurnal Sistem Cerdas, 2024)
Research on automatic port inspections using robots has been carried out in the state-owned company Indonesia Port Corporation, Semarang, Indonesia. However, increasing the efficiency of robotic inspections is critical because robots need to perform these tasks at much higher speeds than humans, while maintaining a high level of accuracy. The robot is equipped with sensors and computer vision technology to detect defects or problems that humans might miss. The aim is to increase overall inspection accuracy at a lower cost. In this research, we introduce an optimized A* path planning algorithm that incorporates the flood algorithm, node reductions process, and linear path planning optimization for an autonomous navigated port inspection robot. Our primary objective is to significantly increase the efficiency of the conventional A* algorithm in guiding robotic systems through complex paths. The proposed algorithm demonstrates exceptional efficiency in generating feasible paths, with success attributed to optimization steps that specifically target reducing node processing and enhancing route finding. The experimentation phase involves a comprehensive assessment of the algorithm using six key parameters: running time, number of nodes, number of turns, maximum turning angle, expansion nodes, and the total distances output. Through rigorous testing, the algorithm's performance is evaluated and compared against seven other current algorithms, namely A*, BestFirst, Dijkstra, BFS, DFS, Bidirectional A*, and Geometric A*. Results from the experiments reveal the algorithm's outstanding running time efficiency, surpassing all other algorithms tested. Notably, it exhibits a remarkable 6.5% improvement over the widely recognized Geometric A* algorithm.